2006
DOI: 10.1016/j.quascirev.2006.02.016
|View full text |Cite|
|
Sign up to set email alerts
|

Severnaya Zemlya, Arctic Russia: a nucleation area for Kara Sea ice sheets during the Middle to Late Quaternary

Abstract: Quaternary glacial stratigraphy and relative sea-level changes reveal at least four expansions of the Kara Sea ice sheet over the Severnaya Zemlya Archipelago at 791N in the Russian Arctic, as indicated from tills interbedded with marine sediments, exposed in stratigraphic superposition, and from raised-beach sequences that occur at altitudes up to 140 m a.s.l. Chronologic control is provided by AMS 14 C, electron-spin resonance, green-stimulated luminescence, and aspartic-acid geochronology. Major glaciations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 73 publications
6
49
0
Order By: Relevance
“…4, 19), similar to many other coastal stratigraphic sites in the Arctic [e.g. 6,73]. The depositional processes at Kongsfjordhallet range from suspension settling and mass movements in lower energy (deeper) settings, to wave reworking in higher energy (shallower) environments.…”
Section: Marine and Littoral: Vital Chronological Keys And Glacial Insupporting
confidence: 65%
“…4, 19), similar to many other coastal stratigraphic sites in the Arctic [e.g. 6,73]. The depositional processes at Kongsfjordhallet range from suspension settling and mass movements in lower energy (deeper) settings, to wave reworking in higher energy (shallower) environments.…”
Section: Marine and Littoral: Vital Chronological Keys And Glacial Insupporting
confidence: 65%
“…growing season temperature). We present new palaeoenvironmental data based on five disjunct b1 m thick peaty and silty sections, all but one of which were described and sampled on southwestern October Revolution Island, close to the present Vavilov Ice-Cap margin, during a joint Swedish-American-Russian expedition in 2002 (see Möller et al, 2007). The fifth section, located on Bolshevik Island, was previously studied by Raab (2003) and we have added new data to this record.…”
Section: Introductionmentioning
confidence: 98%
“…Although recent palaeoenvironmental studies on the Severnaya Zemlya archipelago have revealed a long and complex history of glaciations and associated sea-level changes from the middle to the late Pleistocene (Bolshiyanov and Makeyev, 1995;Andreev et., al., 1997a;Raab et al, 2003;Möller et al, 2007), relatively little is known about environmental changes during and after the Pleistocene/ Holocene transition (ca. 11,500 cal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether or not this increase in coarse fraction abundance on the Lomonosov Ridge is solely caused by the BarentsKara ice sheet remains an open question. A reconstruction of the Kara ice sheet indicates that there have been major glacial events during at least two earlier Pleistocene glaciations (Möller et al, 2006), which challenges arguments for a local origin of the grain size shift at MIS 6/7 on the Lomonosov Ridge.…”
Section: Links Between Composite Stratigraphiesmentioning
confidence: 97%